2018
DOI: 10.3390/ma11101976
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Acoustic Metasurface with High-Q Spectrum Splitting

Abstract: We propose a tunable acoustic metasurface using a nested structure as the microunit, which is constituted by two distinct resonators. Thanks to the coupling resonance for the microunit and by simply adjusting the rotation angle of the inner split cavity, this nested structure provides nearly 2π phase shift. The full-wave simulations demonstrate that the constructed metasurface can be tuned to reflect incident sound waves to different directions in the operation frequency region with a very narrow bandwidth, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…the volume velocity u across the waveguide's cross-section [17,38]. Figure (1) represents the unit cell and its equivalent circuit [39,40].…”
Section: Electroacoustic Analogymentioning
confidence: 99%
See 1 more Smart Citation
“…the volume velocity u across the waveguide's cross-section [17,38]. Figure (1) represents the unit cell and its equivalent circuit [39,40].…”
Section: Electroacoustic Analogymentioning
confidence: 99%
“…The thermal and viscous effects are assumed to be negligible, which justifies the internal resistance of this part of the circuit being zero. The right part of the circuit is equivalent to an air cylinder, and takes the form of a parallel LC circuit [35,39] consisting of a capacitor C c and an inductance L c . Their expressions can be written as follows:…”
Section: Electroacoustic Analogymentioning
confidence: 99%
“…Thanks to their thinness which is usually in the sub-wavelength, AMs have added value and functionalities in comparison with other acoustic metamaterials with small footprint (Xie et al, 2014;Cheng et al, 2015;Zhao et al, 2017;Assouar et al, 2018;Quan and Alu, 2019). Numerous exotic acoustic phenomena such as sound cloaking (Faure et al, 2016;Ma et al, 2019;Fan et al, 2020;Zhou et al, 2020), sound splitting (Zhai et al, 2018;Ding et al, 2021), sound absorption (Ma et al, 2014;Song et al, 2019;Liu et al, 2021;Li et al, 2022a;Guo et al, 2022), anomalous reflection or refraction (Diaz-Rubio and Tretyakov, 2017;Li et al, 2019a;Zhu and Lau, 2019;Li et al, 2020a;Chiang et al, 2020;Song et al, 2021), sound focusing (Zhu et al, 2016a;Lombard et al, 2022), one-way sound propagation (Zhu et al, 2015;Jiang et al, 2016), and medical ultrasound (Tian et al, 2017;Hu et al, 2022) have been proposed and demonstrated using AMs. AMs possess unusual features, including selective focusing and negative refraction, are enabled by the generalized Snell's law, which adds a new degree of freedom to control the behavior of transmitted or reflected waves by incorporating a lateral momentum (Yu et al, 2011) (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…An acoustic gradient metasurface was established with coiling-up space units, and anomalous reflections at all-angle incidence were obtained [ 26 ]. Zhao and Zhai [ 27 ] designed the AMS with a structure unit with a split cavity and an annular split cavity, and the anomalous modulation of the reflected acoustic waves was attained by changing the rotation angle of the inner split cavity. Liang et al [ 28 ] designed a reflected acoustic hypersurface with Schroeder diffusers based on a subwavelength local resonance unit.…”
Section: Introductionmentioning
confidence: 99%